Assessment of the Trend of Secondary School Students’ Academic Performance in the Sciences, Mathemetics and English: Implications for the Attainment of the Millenium Development Goals in Nigeria - Sakiyo, John (Advances in Social Sciences Research Journal, 2015)
Students’ academic performance in the sciences is crucial for national development and the attainment of the Millennium Development Goals. With a year to the end of the MDGs, this study assessed the trend of students’ academic performances in Biology, Chemistry, Physics, Mathematics and English in West African Senior School Certificate Examination (WASSCE) from 2008 - 2012. The results of the entire students who sat for this examination in Nigeria in the 5 subjects were studied. Ex-Post facto research design was employed in the study. Percentages of students who obtained grade 1 - 6 in the 5 subjects were used to analyse the data. It was found that there was steady increase in the enrolment of students in the 5 subjects however, with fluctuating performances in Biology, Chemistry, General Mathematics and English language, except Physics which recorded an increased performance that fluctuated only in 2009. In terms of average academic performance from 2008 - 2012, physics recorded the best average academic performance with mean of 56.01% followed by English (52.52%), Mathematics (47.44%), Chemistry (46.30%) and the least average academic performance was in biology (37.27%). It was also found that Biology had the highest failure rate of 28.66% followed by Mathematics (24.39%), Chemistry (22.52%), English (21.89%) and the least failure rate was in physics (13.08%). The results also show that from 2008 - 2012 only 46.50% of the students obtained 1 - 6 grades in Biology, Chemistry, Physics, Mathematics and English in WASSCE. The implication of these abysmal performances is that the pace of achieving national development and the MDGs will be slow and difficult. It was recommended that there should be a total overhaul of the teaching and learning process of these subjects.